2012
DOI: 10.1073/pnas.1207670109
|View full text |Cite
|
Sign up to set email alerts
|

Phenanthriplatin, a monofunctional DNA-binding platinum anticancer drug candidate with unusual potency and cellular activity profile

Abstract: Monofunctional platinum(II) complexes of general formula cis-[Pt(NH 3 ) 2 (N-heterocycle)Cl]Cl bind DNA at a single site, inducing little distortion in the double helix. Despite this behavior, these compounds display significant antitumor properties, with a different spectrum of activity than that of classic bifunctional cross-linking agents like cisplatin. To discover the most potent monofunctional platinum(II) compounds, the N-heterocycle was systematically varied to generate a small library of new compounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
311
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 289 publications
(339 citation statements)
references
References 24 publications
5
311
0
1
Order By: Relevance
“…The large, planar aromatic phenanthridine ligand might implicate intercalation as a DNAbinding mode for phenanthriplatin, but analysis of competition Scatchard plots obtained by probing the affinity of ethidium bromide for DNA in the presence of this novel monofunctional platinum compound confirmed that it interacts with DNA in a purely covalent manner [33]. The interaction of phenanthriplatin with DNA in Escherichia coli provided further evidence to support the hypothesis that DNA is the ultimate biological target of this anti-cancer agent (figure 4).…”
Section: (B) Phenanthriplatin: a Potent Monofunctional Complexmentioning
confidence: 90%
See 2 more Smart Citations
“…The large, planar aromatic phenanthridine ligand might implicate intercalation as a DNAbinding mode for phenanthriplatin, but analysis of competition Scatchard plots obtained by probing the affinity of ethidium bromide for DNA in the presence of this novel monofunctional platinum compound confirmed that it interacts with DNA in a purely covalent manner [33]. The interaction of phenanthriplatin with DNA in Escherichia coli provided further evidence to support the hypothesis that DNA is the ultimate biological target of this anti-cancer agent (figure 4).…”
Section: (B) Phenanthriplatin: a Potent Monofunctional Complexmentioning
confidence: 90%
“…A structural analysis of RNA pol II stalled at a site-specific pyriplatin lesion suggested that, by increasing the steric bulk of the N-heterocyclic ligand, it might be possible to increase transcription inhibition and consequential cytotoxicity [32]. From a panel of different N-heterocyclic ligands, Am, a series of complexes having the formula cis-[Pt(NH 3 ) 2 Cl(Am)] + was prepared [33]. The compound for which Am is phenanthridine showed the most significant results and was termed phenanthriplatin (figure 1).…”
Section: Monofunctional Platinum Anti-cancer Agents (A) Pyriplatin: Rmentioning
confidence: 99%
See 1 more Smart Citation
“…The limited doses that can be administered to patients also means that tumors can develop resistance 5 . As such, new drugs continue to be developed to improve the side effect profile and overcome acquired resistance, like phenanthriplatin 6 and phosphaplatin 7 .…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, complexes with other metal ions have become an area of intensive research. The cytotoxic potential of ruthenium complexes was found three decades ago and the utilisation of ruthenium offers several advantages over platinum-based chemotherapy [4,5]. Ruthenium has the ability to mimic iron in binding to biomolecules, which leads to lower toxic side effects and a different mode of action.…”
Section: Introductionmentioning
confidence: 99%